2014
DOI: 10.1038/jcbfm.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot MR Technique to Measure OEF Using Rapid Frequency Mapping

Abstract: Magnetic resonance (MR)-based oxygen extraction fraction (OEF) measurement techniques that use blood oxygen level-dependent (BOLD)-based approaches require the measurement of the R 2 ' decay rate and deoxygenated blood volume to derive the local oxygen saturation in vivo. We describe here a novel approach to measure OEF using rapid local frequency mapping. By modeling the MR decay process in the static dephasing regime as two separate dissipative and oscillatory effects, we calculate the OEF from local frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Our experiments revealed good repeatability of MRI-based OEF measurements among scans. Additionally, OEF is a sensitive surrogate to predict brain tissues at risk 16 26 . In our study, comparison of the OEF map and TTC staining slices showed good consistency between the brain regions with elevated OEF and ischaemic foci on the slices ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments revealed good repeatability of MRI-based OEF measurements among scans. Additionally, OEF is a sensitive surrogate to predict brain tissues at risk 16 26 . In our study, comparison of the OEF map and TTC staining slices showed good consistency between the brain regions with elevated OEF and ischaemic foci on the slices ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of these approaches relies on the measurement of T2* or T2’ relaxation associated with the presence of paramagnetic deoxygenated hemoglobin (deoxy-Hb) in brain tissue (blood oxygen dependent level, BOLD) to measure tissue OEF. 58 An alternative method utilizing a spin tagging technique has been developed, allowing quantification of OEF based on the measurement of T2 relaxation in venous blood. 9,10 However, most applications in these techniques were only for normal subjects, and there were few patient’s studies.…”
Section: Introductionmentioning
confidence: 99%